Genetic Analysis of 17q Terminal Partial Trisomy - Huiling Zheng; Lin Zheng; Zhi Huang; Guangping Li; Daili Tang; Xue Yang; Tian Tian (Clinical Case Reports)
ABSTRACT Chromosomal trisomy syndrome is associated with diverse clinical phenotypes, including intellectual disability. Partial trisomy of the distal 17q is a rare anomaly with similar clinical features, including psychomotor and growth deficits, facial dysmorphism, and microcephaly. Here, we describe three patients from two unrelated families with terminal trisomy 17q. We performed G‐banding karyotype and chromosomal microarray analyses. The child in Family 1 had a 31.3 Mb mosaic duplication on chromosome 17. Family 2 comprised dizygotic twins with a 263 kb deletion on chromosome 15 and a 9.2 Mb duplication on chromosome 17; however, normal karyotyping results were obtained for both parents. We also analyzed the genetic mechanisms underlying the occurrence of these chromosomal aberrations and summarized the literature describing known genotype–phenotype correlations. Given the rarity of partial trisomy of terminal 17q, these cases will provide new insights into the diagnosis of this condition and genotype–phenotype correlations, which can aid in the detection of such conditions and genetic counseling.